Survival Ability And Mental Health Of Women Conflict Survivors In Aceh (1989–2005): A Reflection On Twenty Years Of Peace - Reni Nuryanti; Zaujatul Amna; Ardian Fahri; Bachtiar Akob (Badan Riset dan Inovasi Nasional (BRIN), 2026)
Two decades after the end of the armed conflict in Aceh (1989–2005), issues related to the mental health of women survivors remain highly significant. Military operations conducted during the periods of the Military Operational Zone (DOM), the Humanitarian Pause, Martial Law, and Civil Emergency generated profound trauma that shaped the chronicity of Acehnese women life experiences. This study aims to analyze the forms of survival ability developed by women affected by the conflict and their implications for mental health, drawing on Vigh’s (2008) concept of chronicity. This research employs historical literature studies and fieldwork based on feminist oral history through in-depth interviews and focus group discussions (FGDs) with 42 informants from Pidie, North Aceh, and East Aceh. The findings reveal that women experienced cumulative and multi-layered psychological trauma, manifested as Post-Traumatic Stress Reaction (PTSR), Post-Traumatic Stress Disorder (PTSD), and chronic depression at the same time, women developed survival abilities across four main domains: psychological, social, political, and cultural. The psychological domain is reflected in the optimization of spiritual and emotional coping through religious practices. The social domain is supported by children, families, relatives, communities, and assisting organizations such as Flower Aceh. The political domain is evident in women’s participation in peace movements, while the cultural domain is embodied in local wisdom, including meusare-sare, lullabies such as Dodaidi and Aneuk Yatim, literary works, and traditional dances. These finding confirm that survival abilities rooted in local wisdom and community support play a significant role in strengthening resilience and psychological well-being among women survivors of the Aceh conflict.